Правова природа двосторінніх міждержавних програм на пострадянському просторі - Бабін, Б. В.; Бабин, Б. В.; Babin, B. (My University, 2010)
There are normative content of the interstate programs adopted by the post- soviet states analyzed in the article. The difference of the legal nature of this programs from the agreements, in frames of which they are adopted, is proved, the presence of the normative legal demands in those programs is pointed.
Бабін Б. В. Правова природа двосторінніх міждержавних програм на пострадянському просторі / Б. В. Бабін // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 95-103.
Keywords: двосторонні міждержавні програми на пострадянському просторі; міжнародне право; міжнародна нормотворчість; двухсторонние межгосударственные программы на постсоветском просторе; международное право; международное нормотворчество; bilateral intergovernmental programs in the former Soviet expanse; the international standard-setting; international law